Architecture walks : the best outings near New York City - Rosenfeld, Lucy D., 1939- (Rutgers University Press, 2010)
Welcome to the fascinating world of Architecture Walks--from reflections of three hundred years of history to expressions of the most modern design, authors Lucy D. Rosenfeld and Marina Harrison guide you on a tour of inspiring, informative, and aesthetically intriguing architectural treasures in and around the New York area. Early colonial saltboxes, as-yet-unfinished contemporary structures on college campuses, nineteenth-century follies, Gilded Age palaces, lighthouses, windmills, romantic ruins-- the pages of this delightful book, filled with adventures, treat readers to sites within approximately two hours' driving time from New York City. With book in hand readers will marvel at college campuses, small villages, planned and utopian communities, National Historic Sites, castles and forts, churches and temples of architectural interest, and even a Buddhist monastery, all in Connecticut, New York, New Jersey, the eastern edge of Pennsylvania, and Delaware. By including descriptions of architectural styles, suggestions for special adventures, and lists of jaunts arranged by architect or designer, architectural style, and particular types of sites, Rosenfeld and Harrison help make day trips even more enjoyable. Whether explorers or armchair adventurers, readers of all ages will find something that captures their interest in the nearly one hundred sites and forty photos included in Architecture Walks.